Membangun Masyarakat yang Islami - Efendy, Erwan; Kurniawan, Rhohis; Br Ginting, Nadia Shaliha (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
Islam is a perfect religion with teachings in it that create happiness and prosperity for its adherents but unfortunately there are still many people who have not embraced Islam, and moreover it is very unfortunate that people who have embraced Islam still do not want to practice Islamic teachings let alone to preach, spread them, Therefore, it is very necessary to carry out da'wah activities that are able to build an Islamic society, so that later it is expected to be able to create a prosperous and happy community life. Da'wah that can be carried out includes words of invitation, examples of deeds and with writings like those in this journal writing, in which there is an explanation of how to build a real Islamic society, and in order to truly realize an Islamic society, practice is needed so it's not just a theory of service, and of course the need for unity from the Muslims themselves, because Muslims will be strong by uniting and helping each other, an Islamic society will be built. Key words: Islam, Da'wah, Unity.